Spatial distribution of Dechlorane Plus and dechlorane related compounds in European background air - Skogeng, Lovise P.; Lunder Halvorsen, Helene; Breivik, Knut; Eckhardt, Sabine; Herzke, Dorte; Moeckel, Claudia; Krogseth, Ingjerd S. (Frontiers in Environmental Science, 2023)
The highly chlorinated chemical Dechlorane Plus (DP) was introduced as a replacement flame retardant for Mirex, which is banned through the Stockholm Convention (SC) for its toxicity (T), environmental persistence (P), potential for bioaccumulation (B) and long-range environmental transport potential (LRETP). Currently, DP is under consideration for listing under the SC and by the European Chemical Agency as it is suspected to also have potential for P, B, T and LRET. Knowledge of atmospheric concentrations of chemicals in background regions is vital to understand their persistence and long-range atmospheric transport but such knowledge is still limited for DP. Also, knowledge on environmental occurrence of the less described Dechlorane Related Compounds (DRCs), with similar properties and uses as DP, is limited. Hence, the main objective of this study was to carry out a spatial mapping of atmospheric concentrations of DP and DRCs at background sites in Europe. Polyurethane foam passive air samplers were deployed at 99 sites across 33 European countries for three months in summer 2016 and analyzed for dechloranes. The study showed that syn- and anti-DP are present across the European continent (